Switching Therapy to the Second Brand of Generic Atorvastatin: A 6-Month Retrospective Cohort, Real-World Study - Panisa Manasirisuk; Somsak Tiamkao; Chaiyasith Wongvipaporn; Nanthaphan Chainirun; Kittisak Sawanyawisuth (Drugs - Real World Outcomes)
Abstract Introduction High levels of low-density lipoprotein-cholesterol (LDL) is a major risk factor for cardiovascular diseases. While treatment with atorvastatin is beneficial, the original atorvastatin may be cost prohibitive to some patients. Currently, a second brand of generic atorvastatin is available on the market. This study aimed to evaluate the effectiveness of the second generic brand of atorvastatin. Methods This was a retrospective cohort study conducted at Khon Kaen University Hospital, Thailand. The inclusion criteria were adult patients who received either Xarator® (original atorvastatin; Pfizer Pharmaceuticals, Puerto Rico) or Atorvastatin Sandoz® (Lek Pharmaceuticals, Slovenia) for at least 3 months prior to switching therapy to the second brand: Lipostat® (Siam Pharmaceutical, Thailand). The study period was between 1 April 2022 and 30 June 2023. The primary outcome of this study was a change in LDL 6 months after switching therapy from either the original (Xarator®) or generic atorvastatin (Atorvastatin Sandoz®). Results There were 683 patients who switched therapy from the original atorvastatin (Xarator®), and 1044 patients who switched therapy from generic atorvastatin (Atorvastatin Sandoz®), for a total of 1727 patients. Regarding LDL levels, switching therapy from original atorvastatin (Xarator®) resulted in a slightly lower but not significant decrease in LDL at 6 months (− 0.96 mg/dL; 95% CI of − 3.20, 1.28), while switching therapy from generic atorvastatin (Atorvastatin Sandoz®) led to significantly lower LDL at − 3.30 mg/dL (95% CI of − 5.25, − 1.36). The original (Xarator®) and generic atorvastatin (Atorvastatin Sandoz®) group also resulted in a significantly lower estimated glomerular filtration rate at − 0.90 and − 1.21 mL/min/1.73 m2, respectively, from baseline. Conclusions The second generic atorvastatin (Lipostat®) resulted in comparable outcomes on LDL compared with the original (Xarator®), but significantly lower LDL levels than another generic atorvastatin (Atorvastatin Sandoz®) 6 months after switching therapy. However, renal function should be closely monitored.